Malnutrition in hospitalized pediatric patients: A comparison of the National Turkish and World Health Organization (WHO) child growth standards [Hastanede yatarak tedavi gören Çocuklarda malnütrisyon: Ulusal Türk ve dünya saǧlık örgütü (DSÖ) çocuk büyüme standartlarının karşılaştırılması] - (:unkn) unknown (Marmara University, 2012)
Objective: Malnutrition is known to be responsible for mortality especially in hospitalized children. Since there is a controversy regarding the criteria used to define malnutrition worldwide, the World Health Organization (WHO) has recommended using z-scores and has reported that the WHO child growth standards have worldwide validity. The aims of this study were to evaluate the prevalence of malnutrition in hospitalized pediatric patients and compare the Neyzi growth standards used in Turkey with the WHO standards. Patients and Methods: Weight-for-age, weight-for-height, and height-for-age were calculated separately in patients under five years old using the national Neyzi standards and the WHO 2006 standards. The weight-for-age-and height-for-age z-scores were also calculated, and malnutrition was defined as < -2 SD. Results: Among the 100 patients included in the study, 62 were male, and the mean age was 15.9±16.2 months. Twelve percent of the patients were classified as acute malnutrition, 13% were classified as chronic malnutrition, and 11% were underweight. The calculated mean weight-for-age and height-for-age z-scores were significantly different between the two growth standards (p<0.001). Conclusion: Although WHO has reported that the new WHO growth standards are applicable in all countries, there was a discrepancy between the WHO-and country-specific growth charts, and this presents a major problem for the evaluation of malnutrition. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Child; Hospital; Malnutrition; Z-score